Audio Description of Theatrical Performances: History, Peculiarities and the Guidelines of Audio Introduction - Niedzviegienė, Laura (Respectus Philologicus, 2017)
The article discusses the peculiarities, development and prevalence of the audio description methodology of theatrical performances in different countries. Special attention is paid to the review and analysis of emerging traditions of the methodology of audio description of theatrical performances in Lithuania, since any scientific articles discussing this subject in detail have not yet been published in our country. The article examines the audio introduction (AI) text of Panevėžys Juozas Miltinis Drama Theatre performance Vyšnia šokolade (directed by Linas Marijus Zaikauskas). The AI text is based on the AI guidelines defined in foreign countries and drawn by the 3rd year Bachelor’s Degree students of Audiovisual Translation (Vilnius University Kaunas Faculty of Humanities) under the supervision of lecturer Dr. Laura Niedzviegienė. The issues of the preparation of the AI text are discussed and possible solutions are proposed. Furthermore, the author of the article provides general guidance on preparing the audio introductions of theatrical performances for visually impaired people living in Lithuania.